The Role of the Community in Developing the Tourism Potential of Taeno Waterfall, Rumahtiga Village, Taeno Hamlet - Inge Cesilia; Elsina Titaley; Rais R. Haulussy (Populis: Jurnal Ilmu Sosial dan Ilmu Politik, 2026)
This study examines the role of the community in developing the tourism potential of Taeno Waterfall located in Negeri Rumahtiga, Dusun Taeno. The research aims to analyze community participation in tourism development, identify supporting and inhibiting factors, and evaluate its contribution to local socio-economic development. The study employed a qualitative descriptive method through observation, interviews, and documentation involving local residents, community leaders, and related stakeholders. Data were analyzed using data reduction, data presentation, and conclusion drawing techniques. The findings indicate that the community plays an important role in maintaining environmental sustainability, improving tourism facilities, promoting local tourism attractions, and supporting visitor services. Community involvement has contributed to increasing public awareness of tourism potential and creating opportunities for local economic improvement. However, several challenges remain, including limited infrastructure, inadequate government support, and the lack of integrated tourism management. The novelty of this study lies in its emphasis on community-based tourism development in a local rural context, highlighting the importance of participatory approaches in sustainable tourism management. The study concludes that active community participation is a key factor in optimizing the tourism potential of Taeno Waterfall. Therefore, collaboration between the community, government, and other stakeholders is necessary to strengthen sustainable tourism development and support the advancement of social and political studies, particularly in the fields of community empowerment and local tourism governance.